A Goldenhar Syndrome described in neonatal period: case report - Elkıran, Özlem; Yılmaz, Erdal; Kurt, Neşe Çıtak; Akarsu, Saadet; Kurt, Abdullah; Aygün, Denizmen (Bolu Abant İzzet Baysal Üniversitesi, 2012)
Oculo-aurikulo-vertebral syndrome also referred to as Goldenhar Syndrome is a rare condition described initially by Goldenhar in 1952. Goldenhar Syndrome is a wide spectrum of congenital anomalies that involves structures arising from the first and second branchial arches. The syndrome is characterized by anomalies of the ear, hemifacial microsomia, and defects of the vertebral column. The etiology of this rare syndrome is not understood completely and seems to be heterogeneous. Management of Goldenhar syndrome requires a multidisciplinary approach to provide most appropriate treatment. Here we report a newborn with Goldenhar Syndrome who presented all classical signs of this rare condition.

Goldenhar sendromu olarak da bilinen okülo-aurikulo-vertebral sendrom, ilk kez 1952 yılında Goldenhar tarafından tanımlanmıştır. Goldenhar sendromu birinci ve ikinci brankiyal yarıktan köken alan yapıların konjenital anomalilerini içerir. Kulak anomalileri, hemifasiyal mikrosomi ve vertebral kolon anomalileri ile karakterizedir. Sendromun nedeni tam olarak bilinmemekle birlikte heterojen kaynaklı olduğu düşünülmektedir. Goldenhar sendromunun yönetimi, en uygun tedaviyi sağlamak için multidisipliner yaklaşım gerektirir. Burada sendromun tüm klasik bulgularına sahip Goldenhar sendromlu yenidoğan vakası sunuldu.
Yenidoğan döneminde tanımlanan Goldenhar Sendromu: Olgu sunumu